Between the virtual and the real: A brief comment on the simplified and virtual child support process - Bocanegra Risco, Tania Carolina (2020)
Since the growing health crisis produced by COVID-19, our economic, social, and judicial environment has undergone several changes. Among these changes are the measures adopted by the judiciary to continue protecting rights and to continue with «normality» in its own work. This article comments on Directive No. 007-2020-CE-PJ approved by Administrative Resolution of the Executive Council of the Judiciary No. 000167-2020-CE-PJ, which implemented the «Simplified and Virtual Process of Food for Children and Adolescents». Indeed, it will be analyzed its main scopes and relevant modifications with regards to the traditional process. Likewise, the experience of the Superior Court of Justice of La Libertad with respect to the implementation of the virtual form of food demand will be taken into consideration.